Captivity in Hispanic-Comanche Relations, 1700-1821 - Rivaya Martínez, Joaquín (Cuadernos de Historia Moderna, 2025)
This essay explores Comanche-Spanish relations in northern New Spain (today’s US Southwest and northern Mexico) through the lens of captivity. Apart from archival documents, my research incorporates interviews with Native consultants, and ethnographic, archeological, linguistic, and environmental evidence. Comanches and Spaniards seized captives for similar purposes, mostly as labor. Both societies participated in, and benefited from, the captive traffic. The ebb and flow of this traffic reflects changing geopolitical scenarios in the borderlands of northern New Spain. Some captives played key roles in the relations between both peoples. Captivity affected the relations between Spaniards, Comanches, and other Indigenous groups at the local and regional levels, sometimes with reverberations on a continental scale. Both societies offered avenues for the captives’ social promotion toward full incorporation, although stigmatization sometimes persisted. Both groups had little tolerance for the captivity of their own people, which led to a significant increase in violence whenever their respective tolerance thresholds were crossed.
Keywords: captivity; borderlands; northern New Spain; Comanches; indios b´árbaros